Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Siswa Literasi Digital di Era Modern - Leli Hasanah Lubis; Irhamuddin; Fatimah Purba; Marzaniatun; Monica Mulyani Batubara (Insan Zenius Ilmiah, 2025)
The development of digital technology has had a significant impact on the world of education, including the learning process of Islamic Religious Education (PAI). PAI teachers are required not only to master religious material but also to possess digital literacy skills to be able to guide students in facing the challenges of the modern era. Digital literacy in this context goes beyond the technical ability to use technology, but also encompasses ethical, critical, and religious understanding of media. Thus, PAI teachers play a crucial role in shaping a generation that is not only digitally literate but also able to use technology wisely in accordance with Islamic values. This study used a library study method by reviewing various literature related to digital literacy, the role of teachers, and Islamic education. The results of the study indicate that PAI teachers have a strategic role in three main aspects: as guides of digital ethics, facilitators of technology utilization in learning, and role models in the wise use of digital media. This aligns with the needs of education in the era of the Industrial Revolution 5.0, where technological mastery must be balanced with the instilling of spiritual and moral values. Challenges that arise include limited teacher digital competence, limited resources, and the rapid flow of negative information that has the potential to damage students' character. However, with the right strategies such as integrating Islamic digital literacy into learning, digital training for teachers, and collaboration with parents, Islamic Religious Education teachers can shape a digitally literate generation that is intelligent and has an Islamic character, so that they are ready to face the complex dynamics of global life.